Amelanotic/hypomelanotic lentigo maligna: Dermoscopic and confocal features predicting diagnosis. (17th October 2022) - Pizzichetta, Maria A.; Polesel, Jerry; Perrot, Jean L.; Rubegni, Pietro; Fiorani, Diletta; Rizzo, Arianna; Stanganelli, Ignazio; Magi, Serena; Mazzoni, Laura; Medri, Matelda; Dominici, Michele M.; Toffolutti, Federica; et al.
Abstract: Background: Amelanotic/hypomelanotic lentigo maligna and lentigo maligna melanoma (AHLM/LMM) may be very difficult to diagnose at an early stage. Objectives: To quantify the predictive value of dermoscopic and reflectance confocal microscopy (RCM) features for AHLM/LMM. Methods: Dermoscopic and RCM images of histopathologically diagnosed AHLM/LMM, amelanotic/hypomelanotic benign lesions (AHBL), and amelanotic/hypomelanotic basal and squamous cell carcinomas (AHBCC/AHSCC) of the head and neck from consecutive patients were retrospectively collected and blindly evaluated by three observers to assess presence or absence of dermoscopic and RCM criteria. Results: Overall, 224 lesions in 216 patients including LM/LMM ( n = 55, 24.6%), AHBL ( n = 107, 47.8%) and AHBCC/AHSCC ( n = 62, 27.7%) were analysed. Multivariable analysis showed that milky‐red areas (OR = 5.46; 95% CI: 1.51–19.75), peripheral light brown structureless areas (OR = 19.10; 4.45–81.96), linear irregular vessels (OR = 5.44; 1.45–20.40), and asymmetric pigmented follicles (OR = 14.45; 2.77–75.44) at dermoscopy, and ≥3 atypical cells in five fields (OR = 10.12; 3.00–34.12) and focal follicular localization of atypical cells at dermo‐epidermal junction (DEJ) (OR = 10.48; 1.10–99.81) at RCM were significantly independent diagnostic factors for AHLM/LMM vs. AHBL. In comparison with AHBCC/AHSCC, peripheral light brown structureless area (OR = 7.11; 1.53–32.96), pseudonetwork around hair follicles (OR = 16.69; 2.73–102.07), and annular granular structures (OR = 42.36; 3.51–511.16) at dermoscopy and large dendritic (OR = 6.86; 3.15–38.28) and round pagetoid cells (OR = 26.78; 3.15–227.98) at RCM led to a significantly increased risk of diagnosing AHLM/LMM. Conclusions: Amelanotic/hypomelanotic lentigo maligna and lentigo maligna melanoma may have the same dermoscopic features of AHM on other body sites, such as milky red areas, peripheral light brown structureless areas and linear irregular vessels. These features, asymmetric pigmented follicles and at RCM ≥ 3 atypical cells in five fields and focal follicular extension of atypical cells at DEJ may help in recognizing AHLM/LMM even when LM conventional features (e.g., obliteration of hair follicles under dermoscopy and large pagetoid cells under RCM) are absent or present only in very small areas of the lesion.